Assessment of Conservation Interventions at Bouleuteria in Anatolia - İpekoğlu, Başak; Tekin, Tuğçe (01. Izmir Institute of Technology, 2022)
Various conservation implementations are carried out in archaeological sites reflecting the settlement characteristics and values of the area where they are located. It is seen that conservation implementations are commonly carried out in theatres, temples, fountains, baths, churches and bouleuteria. Bouleuteria are council buildings generally planned close to the theatre and in connection with the agora. These structures with a public function, where public assembly convened, have a square or semi-circular plan, and are covered. Bouleuteria bear importance as they were frequently used during the Greek and Hellenistic periods. During the Roman period, the need for this type of structure faded away and the existing bouleuteria were utilised as odeions. Some of the bouleuteria are used today for open-air gatherings, and for this reason conservation implementations are carried out. In this study, the architectural features of the Bouleuteria of Iasos, Patara, Ephesus, and Kibyra and the impacts of the conservation implementations were examined. The effects of implementations changed depending on whether the scale of the implementation was partial or comprehensive. The materials and techniques used also varied according to their compatibility with the authentic condition. As a result of the evaluation criteria, it has been determined that conservation of original values at the structure scale can be achieved by making plans depending on the condition of the original remains.

Bulundukları alanın yerleşim özelliklerini ve değerlerini yansıtan arkeolojik alanlarda, çeşitli koruma uygulamaları yapılmaktadır. Koruma uygulamalarının yaygın olarak tiyatro, tapınak, çeşme, hamam, kilise ve bouleuterion yapılarında yapıldığı görülmektedir. Bouleuterionlar, genelde tiyatroya yakın ve agora ile ilişkili planlanan meclis binalarıdır. Halk meclisinin toplandığı kamusal işlevi olan bu yapılar, kare ya da yarım daire planlıdır ve üzeri örtülüdür. Bouleuterionlar, Yunan ve Helenistik dönemlerde sıklıkla kullanılan bir yapı olması ile önem taşımaktadır. Roma döneminde bu yapı türüne gereksinim kalmamış, mevcut bouleuterionlar birer odeon gibi kullanılmıştır. Bouleuterionlardan bazıları, günümüzde açık hava toplantıları için kullanılmakta ve bu nedenle koruma uygulamaları gerçekleştirilmektedir. Bu çalışmada, koruma uygulamaları gerçekleştirilmiş Iasos, Patara, Efes ve Kibyra Bouleuterionlarının mimari özellikleri ve yapılan koruma uygulamalarının, arkeolojik alana ve bouleuteriona etkileri incelenmiştir. Uygulama ölçeğinin kısmi ya da kapsamlı olmasına göre uygulama etkileri değişmektedir. Kullanılan malzeme ve teknikler de özgün durumla uyumlarına göre değişiklik göstermektedir. Değerlendirme kriterleri sonucunda, özgün kalıntıların durumuna bağlı olarak planlamaların yapılması ile yapı ölçeğinde özgün değerlerin korunmasının sağlanabileceği belirlenmiştir.
Anadolu'daki Bouleuterionlarda Koruma Müdahalelerinin Değerlendirilmesi
Thesis (Master)--Izmir Institute of Technology, Conservation and Restoration of Cultural Heritage, Izmir, 2022
Includes bibliographical references (leaves. 167-175)
Text in English; Abstract: Turkish and English
Keywords: Conservation and restoration; Anatolia; Bouleuteria